A contribuição de Monteiro Lobato para a (re)construção de concepções e práticas de educação ambiental das professoras de educação infantil. - Costa, Maria Celina Furtado Bezerra e (2008)
This research aimed to investigate Monteiro Lobato’s contributions to the rebuilding of concepts and practices of Environmental Education of teachers (all women) from Early Childhood Education. Being acquainted with these contributions is vital to the current national momentum in which Environmental Education is seen as a feasible and positive action toward the eco-crisis resulting from modern civilization. The investigation ended with the production of a qualitative research which focused on ethnography, documentary, and bibliography. In this work, Lobato is regarded both as an author and a man and his work is referred to as “Monteiro Lobato weave”. A descriptive analysis is done by bringing this weave to the every-day-life concerning Environmental Education. Field work was done in five Early Childhood Education Centers. Twelve teachers took part in the research. Each of the teachers wrote a text where they related excerpts of Lobato’s stories to Environmental Education. After gathering these texts, the groups got together to discuss, reflect and share ideas. Six children and two teachers were interviewed. Some documents were analyzed, for instance: Early School Teacher; Criteria for an attendance which respects the fundamental rights of children; National Curriculum Reference to Early Childhood Education; Natural and Social Sciences in Early Education from “Teaching and Learning” (Ensinando e Aprendendo) series of books for children. As part of this research, some articles from local newspapers and magazines related to the socio-environmental conditions of the city of Fortaleza were also used. The research also included reading the work of Lobato in order to find the ecological subject. This research affirms that the ideals and ecological sensitivity of Lobato´s “weave” reveal themselves in his stories and confirms that the teachers are open to the issues of Environmental Education; recognize the need for Environmental Education in early childhood education; recognize the need for training in Environmental Education, showed interest in Lobato´s stories and noted Lobato´s “weave” relationship with Environmental Education. Monteiro Lobato is, therefore, an ecological subject who gave great contributions to the rebuilding of concepts and practices of Environmental Education in Early Childhood Education